TOWARD DEVELOPING PRIMARY SCHOOL LEARNERS’ READING SKILLS: AN ANALYSIS OF TOP-DOWN, BOTTOM-UP AND INTERACTIVE APPROACHES. - Mather, Dr Nazarana (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Literacy education internationally is still in crisis. Only a third of 10-year-olds globally are estimated to be able to read and understand a simple written story [Unicef, 2022]. Out of 45 countries who participated in the international PIRLS testing between 2016 and 2021, the data reveals that 28 countries (or 62%) show that in 2021 more children were below minimum reading proficiency than in 2016, with the most noted differences visible in in Azerbaijan, Latvia, Kazakhstan, and South Africa [Saavedra, Fazili, Ning Wong, Geven & Cloutier, 2023]. In SA children are performing poorly against their African counterparts in international tests and in tests conducted within the country [Mather, 2019]. Thus, an obvious choice of research area in attempting to discover causes for this dismal situation is to find out what is happening in terms of learning and teaching every day in the classrooms of our schools. A practical entry point for this is the teaching practices of our teachers, particularly those directly related to reading development of our school children. This desk study sought to gain insight into approaches that can be used to effectively to develop middle school learners’ reading skills. Desk research or secondary research is a research method that involves using already existing data by conducting research through web searches, online platforms, industry reports, or even physical books [Gell, 2020]. In this study rigorous research has been conducted using online platforms such as Sabinet and Ebscohost to source credible, relevant, and current research related to phenomenon that is being investigated. The study further provided an example of how the interactive approach to reading has been applied in a particular context. It was found that the whilst the interactive approach has shortcomings, it has advocated, and can be adapted for most middle school classrooms. It was concluded that some research has been conducted into writing development. However more research about how the different approaches have been applied in different contexts needs to be conducted to provide useful strategies to support learners’ reading skills and go some way in overcoming the literacy crisis.